Labor Market Institutions and the Incidence of Payroll Taxation - Jinyoung Kim; Seonghoon Kim; Kanghyock Koh (Institute of Labor Economics (IZA), 2021)
Despite unambiguous predictions of the canonical model of a competitive labor market, empirical studies on the labor market effects of payroll taxation provide conflicting evidence. Our meta-analysis shows that varying degrees of labor market competitiveness across places and time could be one explanation for the mixed results. We then estimate the labor market impacts of payroll taxation in Singapore, the country with most competitive and flexible labor market among the countries investigated in the literature. By exploiting the sharp reduction in payroll tax rate when workers turn 60, we find that the payroll tax cut in Singapore has a large effect on wages without changes in employment. We provide novel evidence corroborating the canonical model prediction that the welfare costs of social insurance programs financed by payroll taxes can be minimized in a competitive labor market.
Keywords: H24; I31; J22; 330; payroll tax; labor market outcomes; incidence; regression discontinuity design; meta-analysis; labor market competitiveness